A sensitive spectrophotometric determination of tadalafil in pharmaceutical preparations and industrial wastewater samples - Baghdad Science Journal (مجلة بغداد للعلوم, 2013)
A simple, accurate, precise, rapid, economical and a high sensitive spectrophotometric method has been developed for the determination of tadalafil in pharmaceutical preparations and industrial wastewater samples, which shows a maximum absorbance at 204 nm in 1:1 ethanol-water. Beer's law was obeyed in the range of 1-7?g/ mL ,with molar absorptivity and Sandell ? s sensitivity of 0.783x105l/mol.cm and 4.97 ng/cm2respectively, relative standard deviation of the method was less than 1.7%, and accuracy (average recovery %) was 100 ± 0. 13. The limits of detection and quantitation are 0.18 and 0.54 µg .ml-1, respectively. The method was successfully applied to the determination of tadalafil in some pharmaceutical formulations (tablets) and industrial wastewater samples. The proposed method was validated by sensitivity and precision which proves suitability for the routine analysis of tadalafil in true samples.